2021
DOI: 10.3390/geosciences11020058
|View full text |Cite
|
Sign up to set email alerts
|

Development of a New Type of Geodiversity System for the Scoria Cones of the Chaîne des Puys Based on Geomorphometric Studies

Abstract: The aesthetic beauty of a landscape is an integral value reflected in artistic inspiration. Science, in contrast, tries to quantify the landscape using various methods. Of these, geodiversity indices have been found to be a useful approach, and this geomorphological diversity is characterized through derivatives made from digital terrain models (DTM). While these methods are useful, they have a drawback that the value of some landscape features may be underestimated if they have regular forms. For example, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In order to consider fluvial processes as a relevant morphological agent, in particular on flat areas, where topographic attributes are mostly uniform and mass wasting dependent processes less significant, we considered the drainage network. The issue of unrepresented topographic features is common to other settings: Manosso et al (2021) found lower geodiversity on interfluves landforms and in areas with a homogeneous relief in Brazil, and Vörös et al (2021) had similar issues dealing with volcanic features in France.…”
Section: Methodsmentioning
confidence: 99%
“…In order to consider fluvial processes as a relevant morphological agent, in particular on flat areas, where topographic attributes are mostly uniform and mass wasting dependent processes less significant, we considered the drainage network. The issue of unrepresented topographic features is common to other settings: Manosso et al (2021) found lower geodiversity on interfluves landforms and in areas with a homogeneous relief in Brazil, and Vörös et al (2021) had similar issues dealing with volcanic features in France.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, there are many examples of geodiversity quantification in which some abiotic elements are omitted [15,17,20,26]. This does not necessarily mean that the result is wrong, simply showing that their context of development is limited by a framework that depends on the conditions of the method previously shown [3,16,21,[23][24][25].…”
Section: Methodological Constraintsmentioning
confidence: 99%
“…Despite its undeniable importance, geodiversity confronts various methodological challenges, largely due to its multifaceted nature, the multiple ways in which it can be studied, and the various conditioning factors of the results [14]. When comparing various authors, distinctions become evident in terms of the number and types of geodiversity classes and subclasses that they use (i.e., sets of geological elements within a region and the standard criteria used to distinguish between objects), the varying methodologies employed for index calculations, and the disparate scales and sizes of the study areas that they investigate [15][16][17][18][19][20][21][22][23][24][25][26]. Therefore, it becomes crucial to establish a well-defined methodological and informational framework to guide geodiversity assessment.…”
Section: Introductionmentioning
confidence: 99%
“…However, the variability of the cone (e.g., asymmetry) is not reflected. To explore this, the method of sectorization has been introduced ( [38] and this paper). Sectorization is easiest to understand for circular symmetric cones.…”
Section: Sectorizationmentioning
confidence: 99%